Evaluating the effectiveness of reading logs in early literacy programs: a case study of a rural elementary school in Indonesia - Sueb, Sueb; Hidayah, Layli (Jurnal Bidang Pendidikan Dasar, 2025)
The purpose is to evaluate the effectiveness of reading logs and identify alternative literacy activities that are developmentally appropriate for young learners. Using a qualitative case study design, data were collected through classroom observations, document analysis, semi-structured interviews with teachers and librarians, and focus group discussions with students. The findings reveal that while reading logs offer structure for reading practice, they present cognitive, emotional, and practical challenges that reduce students’ reading motivation and comprehension. Many students struggled with summarization tasks, often viewing the logs as a burden. In contrast, alternative activities such as interactive storytelling, drawing, peer discussions, and digital tools were found to be more engaging and effective. The study concludes that integrating diverse and interactive literacy activities better supports early literacy development and fosters a more positive reading experience for young learners.